(İn) Fertilite Yolculuğumuz - Yağcan, Hande; Özöztürk, Sevcan; Kovalı Sezer, Müge; Yanık, Figen; Bağ Ellialtıoğlu, Aysun; Doğan, Ömer Erbil; Okyay, Recep Emre; Güngör, Sultan Seda; Temel Uğur, Günseli; Çavdar Yıldız, Fatma (Academician Publishing Book DOI Portal, 2023)
-